Preparation and Characterization of Cathode Material Mg0.5Ti2(PO4)3 for Magnesium Cells - SUN, JIAN-ZHI (Asian Journal of Chemistry, 2009)
A cathode material for magnesium cells Mg0.5Ti2(PO4)3 was prepared by a solid-state reaction method at 900 °C. Various techniques i.e., TG/DTA, XRD, IR, SEM were used to characterize the reaction and products. The results showed that the product belongs to rhombohedral system with lattice: rhomb-centered, space group R3c and the cell parameters: a = 0.854 nm, b = 0.854 nm, c = 2.070 nm. FTIR spectra studies were carried out and the vibrational bands were assigned. The sample has a spherical morphology that is 10 μm in diameter. Electrochemical magnesium charge/discharge was found possible. The initial discharge capacities for Mg0.5Ti2(PO4)3 is 25.16 mAh g-1 but the capacities decre-ased rapidly with the increase in cyclic number and further efforts are needed to improve its electrochemical performances.